Understanding the Mechanocatalytic Conversion of Biomass: A Low‐Energy One‐Step Reaction Mechanism by Applying Mechanical Force. Issue 16 (12th March 2019) - Amirjalayer, Saeed; Fuchs, Harald; Marx, Dominik
Abstract: On the way to establishing biomass as a renewable and environmentally friendly source to cover the ever‐increasing global demand on energy and chemicals, one great challenge is the efficient depolymerization of cellulose. Enhanced conversion rates have been discovered in ball‐milling experiments, thus opening a mechanocatalytic approach. However, an understanding of the impact of mechanical forces on the acid‐catalyzed cleavage of glycosidic bonds at the molecular level is still missing. Herein, we contribute such fundamental insight based on atomistic modeling. Mechanically stressing the macromolecular backbone radically changes the depolymerization pathway from a complex high‐barrier reaction upon thermal activation to a low‐energy single‐step mechanocatalytic process. In addition to revealing a regioselective increase in basicity under a mechanical force, our results provide molecular‐level explanations of the experimental findings and might therefore guide rational ways to improve such mechanocatalytic processes. Abstract : Use the force : By explicitly considering the influence of mechanical force on the depolymerization of cellulose, a fundamental change in the reaction mechanism as a result of the applied force was revealed. Ab initio calculations provide a detailed picture of the increased reactivity under mechanocatalytic conditions.